Secondary plasma cell leukemia: a multicenter retrospective study of 101 patients. Issue 1 (2nd January 2019) - Jurczyszyn, Artur; Castillo, Jorge J.; Avivi, Irit; Czepiel, Jacek; Davila, Julio; Vij, Ravi; Fiala, Mark A.; Gozzetti, Alessandro; Grząśko, Norbert; Milunovic, Vibor; Hus, Iwona; Mądry, Krzysztof; et al.
Abstract: This multicenter retrospective study included 101 patients (median age 62 years) with secondary plasma cell leukemia (sPCL). The median time from initial multiple myeloma diagnosis to sPCL was 31 months. Fifty-five out of 72 patients (75%) who received any therapy were treated with immunomodulators (IMiDs) and/or proteasome inhibitors (PIs), and 14/72 (19%) underwent salvage autologous stem cell transplantation (ASCT). The overall response rate in patients who received ASCT or PI (either alone or in combination) was higher than in those who did not (93% vs. 36% and 60% vs. 30%, respectively). The median overall survival (OS) in patients who received therapy was 4.2 months (95% CI: 1.3; 8.0) with a 1-year OS of 19%. Platelet count ≤100 × 10 9 /L at sPCL diagnosis was the only independent predictor of a poorer OS in treated patients (HR = 3.98, p  = .0001). These findings suggest that patients with sPCL may benefit from salvage ASCT- and PI-based regimens.